Manejo agronómico del cultivo de Cardamomo (Elettaria cardamomum Linneo) en Ecuador - Salvatierra Salavarria, Victor Urvin (2025)
This research looks at the treatment of the cardamom plan͏ta (Elettaria cardamomum) in Ecua͏dor͏, pointing out the best conditions for its growth, the problems with pests and its economic effect. A simple observation was made without experiments based on reading books. We noticed good ways to care for the plant, looking at things like heat, humidity and soil type. The cactus grows best between 10 and 35 g͏rads Celsius, with rainfall per year between 1500 to 3000 millimeters, and in acidic soils that let water percolate, full of organic matter. We realized that growing with rhizomes is better than setting seeds because it grows more equally and quickly. The big care challenges are insects, such as thrips, borers and grubs as well as fungal diseases such as Fusarium oxysporum and Cercospora an I͏ntegrated Pest Management to help avoid these risks. The study says that cardamom is a viable option in warm and sub-warm places in Ecuador, but sustainable methods must be used, such as analyzing the soil; managing water well; and caring for the wild life, which will help its production and long-term future.